An Exploratory Study of Organizational Governance in Publicly-Quoted Professional Service Firms. Issue 6 (June 2015) - Pickering, Mark E.
There has been a trend of large professional service firms (PSFs) to move from the partnership form of ownership to alternative ownership forms. As part of this trend large, publicly-quoted accounting companies have emerged in Australia, the US and the UK. Research on how publicly-owned PSFs, including accounting companies, are governed, whether aspects of the governance of partnership persist, why particular governance interpretive schemes and associated structures and systems are implemented and implications for performance is sparse. This study explores the interpretive scheme of governance in two Australian publicly-quoted accounting companies and finds one of the companies to have mimicked the major attributes of the partnership interpretive scheme while the other company moved to a corporate form of governance eliminating all vestiges of the partnership interpretive scheme. Governance was found to have significant implications for the performance of the companies with moving from a partnership interpretive scheme contributing to the ultimate failure of one of the companies. The cases suggest that failed experiments in the governance of publicly-owned PSFs, a relatively recently emerged ownership form in some professions, may contribute to conflicting prior findings on the implications of ownership form for the performance of PSFs. Two alternative approaches to the introduction of corporate style governance structures and systems were identified with the findings suggesting potential benefits of evolution rather than revolution. Based on the findings, a theoretical model of the interpretive scheme of governance of publicly-traded PSFs is developed including factors affecting the interpretive scheme implemented and the introduction of more corporate-like governance structures and systems, potential performance implications of PSFs moving away from a partnership interpretive scheme and the conditions and contingencies under which the relationship may hold. The paper also extends the application of agency theory to publicly-owned PSFs.